2019
DOI: 10.1590/interface.180617
|View full text |Cite
|
Sign up to set email alerts
|

Impasses e desafios para consolidação e efetividade do apoio matricial em saúde mental no Brasil

Abstract: Passados dez anos da implementação do apoio matricial nas redes de saúde por meio dos Núcleos de Apoio à Saúde da Família, ainda sente-se a falta de dados consistentes quanto à consolidação e efetividade desse arranjo. Nesse sentido, este estudo teve como objetivo revisar a bibliografia nacional dos últimos dez anos a fim de identificar os impasses e desafios vivenciados no apoio matricial em saúde mental na Atenção Primária, classificando-os a partir de uma reconstrução teórico-conceitual e fazendo uma articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
43

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 41 publications
0
24
0
43
Order By: Relevance
“…There may be several factors that lead to the di culty of operating this service. A literature review conducted previously [9] suggested that although it has been over 10 years since the implementation of matrix support in the Brazilian health system, it remains common for health networks to face problems such as: 1) lack of clarity in guidelines regarding the sharing of cases; 2) bureaucratization of the referral between services; 3) negative attitudes of professionals in dealing with mental health related issues; and 4) lack of institutionalized space and time for sharing of cases. It is noteworthy that these aspects are also highlighted in the study of international counterparts of this methodology, such as shared care [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be several factors that lead to the di culty of operating this service. A literature review conducted previously [9] suggested that although it has been over 10 years since the implementation of matrix support in the Brazilian health system, it remains common for health networks to face problems such as: 1) lack of clarity in guidelines regarding the sharing of cases; 2) bureaucratization of the referral between services; 3) negative attitudes of professionals in dealing with mental health related issues; and 4) lack of institutionalized space and time for sharing of cases. It is noteworthy that these aspects are also highlighted in the study of international counterparts of this methodology, such as shared care [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, although there have been signi cant contributions to the literature regarding facilitators and barriers to matrix support services [7,8], little is known about the system's quantitative impact on the sharing of cases between different levels of care [9].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently with its historical backstepping, the ill-advised ruling reestablished in the RAPS a secondary level of care through specialized mental health teams, opening the way for reinstalling hierarchical and stand-alone psychiatric outpatient clinics. This again shows the field's active inclination towards the hegemony of biomedical practices, since the adequate implementation of Centers to Support Family Health (NASF) would solve the linkage between levels of care, as shown by some recent studies 10 .…”
mentioning
confidence: 83%
“…Agora em 2020, deve atingir entre 15% e 20% da população mundial. A depressão ocupará o 2º lugar na referida classificação, perdendo apenas para as doenças cardíacas (1,3,4) . O termo depressão era usado, inicialmente, para designar sintomas ou caracterizar estados mentais, sendo que o nome da doença era melancolia, termo cunhado há mais de 25 séculos; que, além de indicar uma das doenças mentais, também correspondia a um tipo de temperamento, um estado emocional baixo, infeliz, desanimado e triste (3,5) .…”
Section: Introductionunclassified
“…De acordo com Farias (6) , as principais classes terapêuticas no campo da saúde mental seguem o seguinte percentual: 28% dos medicamentos dispensados são antidepressivos, 24% benzodiazepínicos, 21% antiepilépticos, 10% antipsicóticos, 8% barbitúricos, 6% analgésico de ação central, 2% antiparkinsoniano e 1% inibidor de receptor H1. A depressão será a doença mais comum no mundo em 2030 (1,3,4) . Neste contexto, este trabalho teve como objetivo conhecer o perfil de utilização de medicamentos pelos utentes do Serviço de Assistência Psicossocial (SAPS) do Instituto de Ciências da Saúde (ICS) da Universidade Federal do Pará (UFPA).…”
Section: Introductionunclassified